2017
DOI: 10.2147/dddt.s134518
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin suppresses pancreatic cancer cell growth by upregulating HTRA3 expression

Abstract: Paeoniflorin (PF) is an active monoterpene glycoside extracted from Paeonia lactiflora Pall. PF has exhibited antitumor effects in various cancer types. However, the effects of PF in pancreatic cancer are largely unexplored. Here, we showed that PF suppressed growth of pancreatic cancer cell lines Capan-1 and MIAPaCa-2 and profoundly sensitized these cells to X-ray irradiation. Through microarray analysis, we identified HTRA3, a tumor-suppressor candidate gene, as the most increased gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Based on studies performed in recent years, it is found Paeoniflorin combined with gemcitabine inhibits pathways EGFR/MAPK/ERK and ErbB3/PI3K/Akt, and increases proliferation of pancreatic cancer cell ErbB3 . Some other studies show that Paeoniflorin in concentration of 1000 μmol/l inhibits growth of pancreatic cancer cell through up‐regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis . In 2018, Huang et al .…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on studies performed in recent years, it is found Paeoniflorin combined with gemcitabine inhibits pathways EGFR/MAPK/ERK and ErbB3/PI3K/Akt, and increases proliferation of pancreatic cancer cell ErbB3 . Some other studies show that Paeoniflorin in concentration of 1000 μmol/l inhibits growth of pancreatic cancer cell through up‐regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis . In 2018, Huang et al .…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
“…[46] Some other studies show that Paeoniflorin in concentration of 1000 lmol/l inhibits growth of pancreatic cancer cell through up-regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis. [47] In 2018, Huang et al [48] found that Paeoniflorin inhibits proliferation of human pancreatic cancer cell Pane-1 and promotes apoptosis, for which the mechanism is probably that the pathway Caspase is activated.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing a drug-targets-pathway network to visualize the pharmacological activity of paeoni orin. For example, breast cancer [44], colorectal cancer [45], glioma [17], pancreatic cancer [46], multi-target potential mechanisms are usually our exploration targets for cancer research. Therefore, paeoni orin may be a promising resource for use as a chemical moiety or active ingredient for future drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…36 Global analysis of gene expression showed that HTRA3 is the most increased gene upon PF treatment in Capan-1 cells; further investigation demonstrated that HTRA3 increases the expression level of Bax, thus inducing pancreatic cancer cell apoptosis. 22 A novel study revealed that by inhibiting prolactin, PF induces prolactinoma cell apoptosis through the mitochondria-dependent pathway, which is related to phosphorylated P53 upregulation. 60 Moreover, PF-induced apoptosis of A549 cells is due to activation of the Fas/Fas ligand apoptotic system, reflected in the increased expression of Fas/apoptosis-1 and its 2 ligands.…”
Section: Cell Cycle Arrestmentioning
confidence: 99%